The family and pre-school collaboration role for the child’s preparation to school - Jankovska, Jekaterina; Prudņikova, Ilga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The child's preparation for school is a period of laying the foundations for a child's future social inclusion. Children's preparation for school is as important a problem as the child's comprehensive development of pre-school age. Preparation for school is a continuous process that starts from the arrival of the child's pre-school and continues until the transition for school. Preparation for school is a socialization process that is child self-determination in the new social environment basis. Socialization, comprehensive child's preparation for school is a very important problem that exists preschools for students with visual impairments. Modern education is a main objective the child's individuality educational support. The child's personality development can be only in a family and pre-school collaboration.